Increase in MMP-9 Expressing CD11b+ cells in a CD44 Dependent Way Reduces Severity of Experimental Autoimmune Encephalomyelitis - Kar, Sujata; Kar, Kalipada (Journal of College of Medical Sciences-Nepal, 2018)
Background: Multiple sclerosis (MS) is a dangerous neurodegenerative disorder. Various aspects of the disease have been studied in experimental animal model. Migration of immune cells to the central nervous system (CNS) is a predominant feature of MS. CD44 molecule has been reported to be involved in many important biological processes including contribution in severing inflammation in experimental autoimmune encephalomyelitis (EAE). Matrix metalloprotease-9 (MMP-9) interaction with CD44 has been well known to be involved in cellular adhesion, transmigration and inflammation. In this study, we were interested to examine the role of phagocytic cells expressing MMP-9 in resolving EAE. Materials and Methods: C57BL/6 WT and CD44 KO mice were used as EAE animal model. The level of phagocytic cells expressing MMP-9 in the secondary lymphoid organs were assessed in EAE induced WT as well as CD44 KO animals. Results: EAE severity was found in CD44 KO group compared to WT. Level of CD11b cells (marker of phagocytic cell) in the peritoneal cells expressing MMP-9 was higher in WT compared to CD44 KO. CD11b stained area found to be greater in WT lymph node compared to CD44 KO. Conclusions: This observation suggests the role of CD44 molecule in modulating the immune scenario which is related to disease severity. This study also opens avenues for the specific inflammatory roles of different immune cells in MS. Keywords: multiple sclerosis; EAE; CD44; MMP-9; CD11b; CNS.